The treatment of men towards women in the works of Che Husna Azhari - Johari, Nenny Djuhara (2007)

(untitled)
This thesis centers on the treatment of men towards women in the Malay society as a document of reality. Through the analysis, the research will portray the works of Che Husna Azhari whereby the women’s characters accept male subjugation and domination. This presents the reality in the society that the author mirrors in her works. The analysis is done through two perceptions. The first part is the perception of Women as Erotic la femme objet where the primary discussion is on women’s sexuality. Another perception is the Women’s Identity. It focuses mostly on the Malay society and Malay women. It is centered on the struggle of the Malay women in finding the balance of her sexuality against social biasness and religious obligation in a patriarchal society This is because the social condition and where these women lived and interact with the society are unique. The analysis will show that the women in Che Husna Azhari’s work lost their will to emancipate themselves because their sacrifices will ensure a better place in heaven and the society. The willingness to be the sacrificial lamb in the altar of marriage is also highlighted. They surrendered their bodies and souls to fulfill the expectations of the society. This is because they have a distorted understanding of women’s role in a true Islamic family and society. In the case of the Malay women, they are also entrapped socially as a result of a misreading of religion and culture. They are also caught in the power struggle to define themselves in a society who places obedience and submission in fulfilling their duty as daughters, wives and mothers. Che Husna’s women show they faced difficulty in finding a balance when dealing with women’s sexuality and identity struggle. The women characters accept the men’s treatment towards them because the men and society expected them to behave as such.